2022
DOI: 10.4315/jfp-21-254
|View full text |Cite
|
Sign up to set email alerts
|

Review and Analysis of Tuna Recalls in the United States, 2002 through 2020

Abstract: This manuscript reviews 18 years of voluntary recalls for commercially sold tuna in the United States. This recall information is a valuable indicator of the failure to implement procedures for food safety. The voluntary recalls involve fresh, frozen, processed, hermetically sealed and retorted in a shelf stable pack (i.e., canned tuna), and formulated into other tuna products. The FDA regulations that regulate the capture, processing, transportation, and sale of raw and processed seafood are discussed. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Although tuna species are considered less allergenic than other often consumed fish species, such as salmon and herring [ 11 , 12 ], the occurrence of parvalbumin is reported in both fresh and processed tuna [ 13 , 14 ]. Due to Blickem et al [ 15 ], undeclared tuna allergen was classified as one of the primary reasons for commercial tuna recalls between 2002 to 2020 in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Although tuna species are considered less allergenic than other often consumed fish species, such as salmon and herring [ 11 , 12 ], the occurrence of parvalbumin is reported in both fresh and processed tuna [ 13 , 14 ]. Due to Blickem et al [ 15 ], undeclared tuna allergen was classified as one of the primary reasons for commercial tuna recalls between 2002 to 2020 in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on recalls have been conducted worldwide. For instance, Blickem et al [28] investigated tuna product recalls in the USA from 2002 to 2020 and emphasized the importance of traceability and food safety culture to prevent recalls. Qiu et al [29] investigated the relationship between food poisoning and recalls in the USA from 2006 to 2016, suggesting that improved traceability may reduce the number of recalls.…”
Section: Discussionmentioning
confidence: 99%
“…27 Undeclared tuna allergen was also classified as a primary cause for commercial tuna recalls in the United States between 2002 and 2020. 28 Numerous studies have reported the heat stability of major fish allergen, parvalbumin (PV; 10-14 kDa), which is present in many different fish species and how it can withstand extensive cooking processes. 29,30 Other highly allergenic fish proteins, such as tropomyosin (TM) and collagens, are also heat stable and are present in wide variety of fish species including Asian seabass (a.k.a.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…While tuna species are generally considered to be less allergenic compared with other commonly consumed fish species like salmon and herring, 3,26 the presence of major allergen has been detected in both fresh and processed tuna 27 . Undeclared tuna allergen was also classified as a primary cause for commercial tuna recalls in the United States between 2002 and 2020 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation